IMPLEMENTATION OF RESTORATIVE JUSTICE IN DISTRICT ATTORNEY’S OFFICE OF ROKAN HULU: CONTEMPORARY ISSUES - Martua, Susanto; Situmeang, Ampuan; Hutauruk, Rufinus Hotmaulana (Universitas Internasional Batam, 2023)
The Attorney General's Office issued Regulation of Attorney General Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice (hereinafter written RAG No. 15/2020). According to this regulation, the Public Prosecutor has the right to stop prosecuting the accused in certain cases, if the victim and the defendant have agreed to an amicable agreement. The existence of RAG No. 15/2020 which gives the Prosecutor's authority to stop prosecutions based on restorative justice is a breakthrough in the settlement of criminal acts. Restorative justice is an approach in resolving criminal acts which is currently being voiced again in various countries. Through a restorative justice approach, victims and perpetrators of criminal acts are expected to achieve peace by prioritizing win-win solutions, and emphasizing that the victims' losses are replaced and the victims forgive the perpetrators of the crime in condition that is committed with the value of the evidence or the value of the loss caused by the crime of not more than 2.5 million rupiah. Referring to the principle of fast, simple, and low-cost justice, RAG Number 15 of 2020 has been accommodated for settlement through an out-of-court process, namely a peace process between the victim and the perpetrator. The peace process is carried out by the parties voluntarily, with deliberation for consensus, without pressure, coercion, and intimidation. In the peace process, the Public Prosecutor acts as a facilitator, which means that he has no interest or connection with the case, the victim, or the suspect, either personally or professionally, directly or indirectly.